1985
DOI: 10.1021/bi00323a040
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of parathyroid hormone responsive cultured human cells on biological activity of parathyroid hormone and parathyroid hormone inhibitory analogs

Abstract: We have employed parathyroid hormone (PTH) responsive human cells cultured from dermis or giant cell tumors of bone (GT) to evaluate the biological properties of a newly developed in vivo PTH inhibitor, [Tyr34]bPTH-(7-34)-amide (PTH-Inh). Short periods of incubation of cells from dermis or GT with maximal stimulatory concentrations of PTH in the presence of increasing concentrations of PTH-Inh resulted in a dose-dependent inhibition of the adenosine cyclic 3',5'-phosphate (cAMP) response (Ki = 3 X 10(-7) M and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…PTH(7-34) is a competitive antagonist to PTH(1-34) and is believed to have no intrinsic activity (22). First, we investigated the capacity of these four PTH peptides to induce PTHR internalization.…”
Section: Prolonged Activation Of the Pthr Results In Increased Molecumentioning
confidence: 99%
“…PTH(7-34) is a competitive antagonist to PTH(1-34) and is believed to have no intrinsic activity (22). First, we investigated the capacity of these four PTH peptides to induce PTHR internalization.…”
Section: Prolonged Activation Of the Pthr Results In Increased Molecumentioning
confidence: 99%
“…However, NTA-(3-34) was found to effectively antagonize the effect of bPTH-(1-34) on uterine contraction and this ac tion was dose dependent [Shew and Pang, 1984], In the same studies a 7-34 PTH frag ment was observed to cause a dose-depen dent increase in uterine contraction [Shew and Pang, 1984). However, since these re- NTA-(3-34) has been shown to be an an tagonist of bPTH-(l-34) in vitro [Rosenblatt et al, 1977;Goldring et al, 1979], When the 1-34 PTH fragment was modified by delet ing the first 6 NH2-terminus amino acids the result was a more potent antagonist of PTH in vitro [Goldring et al, 1983[Goldring et al, , 1985 as well as in vivo [Horiuchi et al, 1983a, b] which was also devoid of PTH-like activity.…”
Section: Discussionmentioning
confidence: 99%
“…The biologically active fragment of PTH consists of the NH2-terminal 34 amino acids ] [Tre gear et al, 1973;Potts et al, 1971Potts et al, , 1982, Shortening this fragment by removing the first six amino acids from the NH2-terminus ] results in a biologically inac tive fragment [Horiuchi et al, 1983a, b]. However, bPTH-(7-34) inhibits both the calcemic effect of bPTH-(l-34) in rats [Doppett et al, 1983] and the bPTH-(l-34)-stimulated accumulation of cyclic AMP in cultured cells obtained from human giant cell tumors of bone and dermis [Goldring et al, 1983[Goldring et al, , 1985,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain data, such as the need for three injections of antagonist in the calcium elevation assay, suggest that the half-life of the antagonist in vivo is less than that of hPTH-(1-34). Data obtained in vitro in cell culture systems support the notion that the antagonist is rapidly degraded at a rate exceeding that of PTH (18 (19). Antagonists that are more effective than [Tyr34]bPTH-(7-34)-amide may be necessary for hormone action to be blocked continuously; the high doses of antagonist required in these studies may not be practical for either extended physiological studies or trials as a diagnostic or therapeutic agent in hypercalcemic disorders in humans.…”
mentioning
confidence: 82%